EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TPS DENGAN PENDEKATAN CTL PADA PEMBELAJARAN MATERI BANGUN DATAR DITINJAU DARI GAYA BELAJAR SISWA KELAS VII MTs KABUPATEN KEDIRI TAHUN PELAJARAN 2012/2013 - Zainal Arifin; Budi Usodo; Sri Subanti (Jurnal Pembelajaran Matematika, 2013)
ABSTRACT: The objectives of this research were to find out: (1) which learning model of the TPS with CTL approach, TPS or conventional learning results in a better learning achievement in mathematics; (2) which students of those with the visual, auditory, and kinesthetic learning styles have a better learning achievement in mathematics; (3) in each learning style, which learning model of the TPS with CTL approach, the TPS, and the conventional learning results in a better learning achievement in mathematics; and (4) in each learning model, which learning style of the visual, auditory, and kinesthetic learning styles results in a better learning achievement in mathematics. This research used the quasi experimental research method with the factorial design of 3x3. Its population was all of the students in Grade VII of Islamic Junior Secondary Schools in Kediri regency. The samples of the research were taken by using the stratified cluster random sampling technique. The samples of the research consisted of 269 students; 86 students belonged to experiment class one, 92 students belonged to experiment class two, and 91 students belonged to control class. The data of the research were gathered through multiple choice test of learning achievement and questionnaire of learning style. The data of the research were analyzed by using the unbalanced two-way analysis of variance at the significance level of 5%. The results of the research are as follows: (1) the TPS with CTL approach and TPS learning models result in the same good learning achievement in mathematics, but both result in a better learning achievement in mathematics than the conventional learning model; (2) the students with the visual, auditory, and kinesthetic learning styles have an equal learning achievement in mathematics; (3) in each learning style, the TPS with CTL approach and TPS learning models result in the same good learning achievement in mathematics, but both result in a better learning achievement in mathematics than the conventional learning model; (4) in each learning model, the students with the visual, auditory, and kinesthetic learning styles have an equal learning achievement in Mathematics.   Keywords: learning model, TPS with CTL approach, TPS, conventional, learning style